2000
DOI: 10.2307/177406
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon Supply and Metabolism in a Shallow Groundwater Ecosystem

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. In groundwater ecosystems, in situ primary production is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
137
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(149 citation statements)
references
References 19 publications
10
137
1
1
Order By: Relevance
“…However, no straightforward insight exists on the role of DOC in groundwater denitrification. Siemens et al (2003) concluded that soil DOC is not an important electron donor in denitrification, whereas Starr and Gillham (1993) and Baker et al (2000) concluded the opposite. The redox reactivity of DOC thus appears to be location-specific, which is in line with the general observation that the biodegradability and composition of DOC in pore water varies (Qualls and Haines, 1992;Artinger et al, 2000;Maurice et al, 2002).…”
Section: Delivery Of Dissolved Carbon and Nutrients To Aquifersmentioning
confidence: 99%
“…However, no straightforward insight exists on the role of DOC in groundwater denitrification. Siemens et al (2003) concluded that soil DOC is not an important electron donor in denitrification, whereas Starr and Gillham (1993) and Baker et al (2000) concluded the opposite. The redox reactivity of DOC thus appears to be location-specific, which is in line with the general observation that the biodegradability and composition of DOC in pore water varies (Qualls and Haines, 1992;Artinger et al, 2000;Maurice et al, 2002).…”
Section: Delivery Of Dissolved Carbon and Nutrients To Aquifersmentioning
confidence: 99%
“…High DOC loading in groundwater can also lead to production of carcinogenic disinfection byproducts during drinking water treatment (Singer 1994;Chomycia et al 2008). Groundwater DOM also serves as a source of carbon and energy for heterotrophic metabolism and drives the bioremediation of many contaminants (Hendriksen et al 1992;McCarty 1997;Baker et al 2000).…”
mentioning
confidence: 99%
“…More recent studies indicate surface plant litter and soil are important sources of DOM in groundwater (Baker et al 2000;Kalbitz et al 2000). Surface precipitation drives the transport of DOM through the soil column to the saturated zone.…”
mentioning
confidence: 99%
“…It may be because organic matter can induce sediment redox in the conditions of nutrient loading, which reduces the absorption of seagrass roots to N, especially nitrate available forms by denitrification from bacterial metabolism (Peralta et al, 2003;Udy and Dennison, 1997b;. In the conditions of higher nutrient loading, denitrification requires a supply of organic matter as energy source (Seitzinger and Nixon, 1985 and its references), resulting in anaerobic respiratory processes (Korom, 1992), which may conversely promote sediment denitrification (Baker et al, 2000;Zhang et al, 2012 and its references). Nutrients absorption of seagrass roots may impact on uptake of seagrass leaves to nitrogen Harlin, 1982, 1984).…”
Section: Negative Effects Of Elevated Organic Matter On Individual Anmentioning
confidence: 99%
“…Denitrification may be heterotrophic, with organic substrates as energy source, with reduced inorganic compounds such as sulfur or iron used as electron donors (Korom, 1992), which was energy source for anaerobic respiratory processes. Anaerobic environment may promote sediment denitrification (Baker et al, 2000;Zhang et al, 2012 and its references). Nutrient enrichment may further intensify the flux of organic matter to the sediment, thereby enhancing the risk of anoxia and sulphide toxicity (Borum et al, 2005;Holmer and Bondgaard, 2001;OlivĂ© et al, 2009;PĂ©rez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%